Application of phase change materials, thermal insulation, and external shading for thermal comfort improvement and cooling energy demand reduction in an office building under different coastal tropical climates. (1st September 2020) - Nematchoua, Modeste Kameni; Noelson, Jean Christophe Vanona; Saadi, Ismaïl; Kenfack, Herves; Andrianaharinjaka, Aro-Zo F.R.; Ngoumdoum, Dominique Foumouo; Sela, Jao Barahimo; Reiter, Sigrid
Highlights: Photovoltaic panels allowed reducing up to 15% of total energy consumption. The comfort rate increases from 2% to 10%, with the installation of PCMs material. The cooling energy reduce of 12.1% with the installation of PCM materials. Abstract: Architectural techniques have evolved over the century. Presently, climatic conditions require architecture that is more adaptable to the environment. Coastal regions have been recognised to be the most vulnerable to the effects of climate change. Thus far, limited research has offered some strategies to mitigate the solar effect on thermal comfort and energy demand in coastal tropical regions. To address this problem, this study was conducted with the aim of evaluating, analysing, comparing, and discussing the impacts of passive strategies on thermal comfort and energy consumption (as well as the introduction of photovoltaic panels) in coastal tropical climate regions. All simulations were conducted for a period of one year using the Design Builder software. The results demonstrate that phase change materials (PCMs) have a significant effect on thermal comfort and energy consumption in an office under different coastal tropical climates. The combination of PCMs with thermal insulation has the ability to increase the comfort rate by up to 3% while decreasing the cooling energy consumption by approximately 12% in three studied climate zones. In a naturally ventilated building, the most significant increase in the comfort rate is observed with the introduction of PCMs in combination with thermal insulation, whereas thermal insulation, along with external shading, results in the most significant reduction in the cooling energy consumption of an air-conditioned office building (approximately 19%) in three studied climates. Furthermore, the introduction of photovoltaic panels enables us to generate 43–79% of the total energy consumption of the studied office building.